The cell cooling coefficient: A standard to define heatrejection from lithium-ion batteries - Hales,A; Diaz,LB; Marzook,MW; Zhao,Y; Patel,Y; Offer,G (Journal of The Electrochemical Society, 2019)
Lithium-ion battery development is conventionally driven by energy and power density targets, yet the performance of a lithium-ion battery pack is often restricted by its heat rejection capabilities. It is therefore common to observe elevated cell temperatures and large internal thermal gradients which, given that impedance is a function of temperature, induce large current inhomogeneities and accelerate cell-level degradation. Battery thermal performance must be better quantified to resolve this limitation, but anisotropic thermal conductivity and uneven internal heat generation rates render conventional heat rejection measures, such as the Biot number, unsuitable. The Cell Cooling Coefficient (CCC) is introduced as a new metric which quantifies the rate of heat rejection. The CCC (units W.K−1) is constant for a given cell and thermal management method and is therefore ideal for comparing the thermal performance of different cell designs and form factors. By enhancing knowledge of pack-wide heat rejection, uptake of the CCC will also reduce the risk of thermal runaway. The CCC is presented as an essential tool to inform the cell down-selection process in the initial design phases, based solely on their thermal bottlenecks. This simple methodology has the potential to revolutionise the lithium-ion battery industry.